2016
DOI: 10.7554/elife.17126
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of methylfarnesoate as the annelid brain hormone reveals an ancient role of sesquiterpenoids in reproduction

Abstract: Animals require molecular signals to determine when to divert resources from somatic functions to reproduction. This decision is vital in animals that reproduce in an all-or-nothing mode, such as bristle worms: females committed to reproduction spend roughly half their body mass for yolk and egg production; following mass spawning, the parents die. An enigmatic brain hormone activity suppresses reproduction. We now identify this hormone as the sesquiterpenoid methylfarnesoate. Methylfarnesoate suppresses trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
87
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(96 citation statements)
references
References 73 publications
(130 reference statements)
8
87
0
1
Order By: Relevance
“…7A). In agreement with Schenk et al (2016), our results also confirmed that annelid MTr is clearly an ortholog of insects and crustaceans MTrs (Fig. 7A).…”
Section: Hormonal Control Of Stolonizationsupporting
confidence: 90%
See 4 more Smart Citations
“…7A). In agreement with Schenk et al (2016), our results also confirmed that annelid MTr is clearly an ortholog of insects and crustaceans MTrs (Fig. 7A).…”
Section: Hormonal Control Of Stolonizationsupporting
confidence: 90%
“…In the annelid C. teleta, exogenous extracts of MF were found to affect larval metamorphosis and settlement (Laufer and Biggers 2001), and MF has been recently demonstrated to be directly involved in P. dumerilii regeneration and female sexual maturation (Schenk et al 2016). This latter study not only showed that the decrease of MF levels in the brain induces reproduction and suppresses regenerative capacities in P. dumerilii, but it also reported an ortholog of the MF receptor of arthropods (bHLH-PAS-domain-containing transcription factor methoprene-tolerant receptor, MTr) in the eleocytes (coelomic cells that synthesize yolk via production of Vtg protein), demonstrating that this hormone is not restricted to arthropods, as it was assumed (Schenk et al 2016).…”
Section: Hormonal Control Of Stolonizationmentioning
confidence: 99%
See 3 more Smart Citations